Libros Para Pueblos: An Exploratory Case Study - Carlyle, Cate; Rehberg Sedo, DeNel D; Rydbeck, Kerstin (Partnership, 2020)
This article is the result of an introductory two-year case study project that investigated community libraries supported by the not-for-profit organization Libros Para Pueblos (LPP) in the state of Oaxaca, Mexico. Libros Para Pueblos (LPP) is a largely volunteer-run library organization based in the capital city of Oaxaca de Juarez. In order to analyse the work of LPP we used Mostert & Vermeulen's (1998) nine areas for evaluation of community libraries. Over the past 20 years, the number of libraries the organization supports has grown from two to more than 70 throughout the state. The work that has facilitated this growth is carried out by a small Mexican staff, along with an Executive Committee and a Board of Directors made up of Americans and Canadians living in Mexico. The work is both time consuming and demanding, but it is fuelled by a positive reading ideology that is a result of memories of childhood reading. This motivation is shared by a network of 11 Mexican Regional Volunteer Coordinators who train and support local library workers. The local workers are often doing their tequio, which is a social requirement of working for one or two years in public service. We argue that the success of LPP libraries is influenced by: 1) an organizational structure that mandates Mexican leadership at the Executive level and in paid staff positions; 2) initiation from local representative; 3) the unique and complex socialist community configurations of the Oaxacan region; 4) a community of retirees who volunteer at many levels; and 5) national and international donations.